2019
DOI: 10.1097/gox.0000000000002381
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits, Anxiety, and Self-esteem in Patients Seeking Cosmetic Surgery in Mexico City

Abstract: Background:There are reports on high psychological morbidity, mainly personality disorders, among people opting for cosmetic surgery. This study aims to describe the personality traits, level of self-esteem, and anxiety in women seeking cosmetic surgery with body contouring, such as liposculpture or lipoabdominoplasty with or without placement of breast implants.Methods:Subjects were 87 women between 18 and 60 years of age in Mexico City who went to a private clinic with the intention of undergoing cosmetic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The prevalence of personality disorders was found to be 53%, which is high when compared with the prevalence in general population in western countries, which is 12.1%. 22 24 Clusters B and C personality disorders are more prevalent in patients who undergo cosmetic surgery, and it also increases the risk for adverse outcomes such as patient dissatisfaction, litigations, and self-harm. 25 The details about personality and associated dimensions are given in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The prevalence of personality disorders was found to be 53%, which is high when compared with the prevalence in general population in western countries, which is 12.1%. 22 24 Clusters B and C personality disorders are more prevalent in patients who undergo cosmetic surgery, and it also increases the risk for adverse outcomes such as patient dissatisfaction, litigations, and self-harm. 25 The details about personality and associated dimensions are given in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
“…It was found that prevalence was greater with interview-based methodology in comparison to standardized tools, which revealed lower rates. 22 23 Anxiety or depressive symptoms before surgery can be misconstrued as a syndromal disorder. Furthermore, the differences in the type of cosmetic surgery might also affect the rates of psychiatric illness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There exists an inadequate number of reports concerning the assessment of personality traits in patients prior to undergoing cosmetic procedures. Participants possessing psychopathological traits in the cosmetic industry were lower than expected, and their levels of anxiety did not cause dysfunction ( 20 ). Integral personality scales have rarely been applied to elucidate aesthetic orientation.…”
Section: Introductionmentioning
confidence: 99%